STRATEGY FOR SOCIALIZATION OF THE GENERAL ELECTION COMMISSION OF PESAWARAN DISTRICT TO REDUCE THE ABSTENTIONS IN THE 2020 ELECTIONS IN PERSPECTIVE OF FIQH SIYASAH - Nur Aini; M. Yasir Fauzi; Rudi Santoso (PRANATA HUKUM, 2023)
The holding of Regional Head and Deputy Regional Head Elections, especially in Pesawaran Regency in 2020 in the midst of the Covid-19 pandemic disaster, threatens many people who abstain from voting. The lack of public participation has caused the number of voters that the Pesawaran Regency KPU wants to achieve to be proof that its performance is still lacking, the disappointment of some people towards the leaders, among other things, gave birth to an attitude of abstaining from voting in elections. The implementation of regional elections is of course the full authority of the Pesawaran Regency KPU, in the midst of the Covid-19 pandemic the Pesawaran Regency KPU must think of a strategy so that public participation in exercising their political rights does not have an impact on the number of abstentions. Socialization is important because the legal basis for holding general elections is always changing and developing, which results in changes to the holding of the general election itself. Theoretically, a rule will apply effectively if it is based on three philosophical validity, namely the ideal principle, juridical validity in the sense that the provisions are made by an authorized institution and sociologically enforceable if these rules can be binding and are recognized effectively by the community , this sociological validity certainly has something to do with the quantity of socialization carried out by officials who are authorized to the existing provisions.